An investigation on the transformation of the decagonal phase to a B2 phase in Al-Cu-Co alloy during mechanical milling - Mukhopadhyay N.K.; Murthy G.V.S.; Murty B.S.; Weatherly G.C. (My University, 2025)
Al65Cu20Co15 decagonal phase, synthesized by a slow cooling technique, were mechanically milled in a high energy planetary ball mill for 10, 20 and 30 h. X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques were used for characterization of phases. The phase transformation from the decagonal phase to a B2-crystalline phase (ordered CsCl type phase) during mechanical milling is reported here for the first time. Powders milled for more than 10 h contained predominantly the B2 type crystalline phase with a lattice parameter of 0.29 nm. This crystalline phase was found to be quite stable after 30 h of milling and also on subsequent annealing at 600°C. These experimental results lend support to an earlier suggestion that the decagonal phase in Al-Cu-Co is actually less stable than the B2 phase at low temperatures. © 2002 Elsevier Science B.V. All rights reserved.